Late‐Stage Hydrocarbon Conjugation and Cyclisation in Synthetic Peptides and Proteins. (15th March 2021) - de Araujo, Aline D.; Nguyen, Huy T.; Fairlie, David P.
Abstract: The conventional S ‐ alkylation of cysteine relies upon using activated electrophiles. Here we demonstrate high‐yielding and selective S‐alkylation and S‐lipidation of cysteines in unprotected synthetic peptides and proteins by using weak electrophiles and a Zn 2+ promoter. Linear or branched iodoalkanes can S‐alkylate cysteine in an unprotected 38‐residue Myc peptide fragment and in a 91‐residue miniprotein Omomyc, thus highlighting selective late‐stage synthetic modifications. Metal‐assisted cysteine alkylation is also effective for incorporating dehydroalanine into unprotected peptides and for peptide cyclisation via aliphatic thioether crosslinks, including customising macrocycles to stabilise helical peptides for enhanced uptake and delivery to proteins inside cells. Chemoselective and efficient late‐stage Zn 2+ ‐promoted cysteine alkylation in unprotected peptides and proteins promises many useful applications. Abstract : Strength in weakness : Selective and high‐yielding late‐stage modifications to unprotected synthetic peptides and proteins are enabled by S‐alkylation of cysteine by using weakly electrophilic alkyl halides and zinc complexes. Under neutral conditions, iodoalkanes do not compromise selectivity for cysteine: Zn 2+ can bind other amino acids but only Cys is alkylated.